Pengaruh Good Corporate Governance, Leverage, dan Ukuran Perusahaan terhadap Nilai Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia - Yusrina Dzakiroh; Novi Khoiriawati (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the influence of good corporate governance, leverage, and firm size on firm value in financial sector companies listed on the Indonesia Stock Exchange in 2019–2020. This study uses a panel data regression analysis with the Eviews 9.0 application. The results of this study indicate that the good corporate governance variable projected by the board of directors has a significant positive effect on firm value, the good corporate governance variable projected by the board of commissioners has a significant negative effect on firm value, and the leverage and firm size variables have no effect on firm value. The conclusion of this study is that good corporate governance, leverage, and company size simultaneously or together have a significant influence on company value in financial sector companies listed on the Indonesia Stock Exchange in 2019–2020.